Relationship of vascular pathology, demographic and radio-anatomical features in aortic dissections detected by multidetector CT - Yusuf Secgın; Serkan Oner; Zulal Oner (National Scientific Medical Center, 2021)
Aim: Aortic dissection is a cardiovascular disease with low incidence but high mortality. The aim of our study is to evaluate the demographic, vascular pathologic and radio-anatomic features of aortic dissection and find out the relationship of these with aortic dissection. Methods: One female and 12 male patients admitted to the hospital with severe chest pain and diagnosed with aortic dissection by Computed Tomography were included in this study. Patients were divided into three groups according to the De Bakey classification. Type I: starting from the ascending aorta and ending in the thoracic aorta, Type II: starting from the ascending aorta and ending in the brachiocephalic artery, Type III: starting from the subclavian artery and ending at the level of the diaphragm and abdomen. Results: The highest aortic dissection incidence was found in group Type III with 54%. The ages of patients with aortic dissection were 56.67±12.50, 61.00±11.53 and 52.00±12.26, respectively according to the groups. According to the Pearson Correlation test, significant correlations were found between ascending aorta and age and aortic arch, between cardiothoracic ratio and heart width, and between thoracic width and thoracic aorta (p≤0.05). One Way Anova test was used for the analysis between dissection groups and significant correlation was found between Type II and Type III groups of ascending aorta parameter (p≤0.05). In addition, it was found that 54% of the patients had mild atherosclerosis and 46% had lumen. Conclusion: A significant relationship was found between aortic dissection and radio-anatomic parameters, demographic and vascular pathologic features.